Producing specific knowledge about news construction: the context of Malaysia - Siti Suriani Othman; Lee, Kuok Tiung; Liana Mat Nayan (ARF Publication Sourcing, Islamabad, Pakistan, 2013)
This paper demonstrates how news construction studies should be conducted by cherishing the specificity of news practices even if the newspapers operate in the same country. Based on Donna Haraway’s notion of specificity and situated knowledge, we argue that in order to understand the complexity of news construction in Malaysia, the study has to recognize the ‘specificity’ and ‘situatedness’ of scientific knowledge of journalism. For that, we first discuss Western influence in journalism studies and the effort of de-Westernization (thus a more specific form of knowledge), the notion of ‘specificity’ and ‘situated knowledge’ and the findings of the study to demonstrate that even in Malaysia, news construction has been a very ‘specific’ practice among different newspapers. In-depth interviews have been conducted with Malaysian editors to understand the heterogeneity of news construction practice, thus supporting the argument on the necessity to produce specific knowledge about news construction in the context of Malaysia.